VD_FINDINFO HC / 2012 / 746 vom 31. Oktober 2012 - VD Tribunal cantonal (2012)
MESURE PROVISIONNELLE, EXÉCUTION FORCÉE, COMPÉTENCE RATIONE MATERIAE | 267 CPC (CH), 319 let. b ch. 1 CPC (CH), 338 CPC (CH)